Low temperature physics - LT 13: proceedings - 475942 International Conference on Low. Termperature Physics, 13th. University of Colorado, 1972; Timmerhaus, K. D.; O'Sullivan, W. J.; Hammel, E. F. (New York: Plenum Press, 1974)
41